2020
DOI: 10.2196/13726
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in the Evaluation of a Virtual Health Agent’s Appearance and Embodiment in a Health-Related Interaction: Experimental Lab Study

Abstract: Background Assistive technologies have become more important owing to the aging population, especially when they foster healthy behaviors. Because of their natural interface, virtual agents are promising assistants for people in need of support. To engage people during an interaction with these technologies, such assistants need to match the users´ needs and preferences, especially with regard to social outcomes. Objective Prior research has already det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Studies were most often published in conference proceedings in fields related to interdisciplinary research on intelligent virtual agents and human-computer interactions, with fewer published in health-related fields. No significant effect [48] a , [51] No significant effect [48] a , [51,62] No significant effect [48] a Mixed negative [48] a , [62] 3 (7) Animated avatar (vs no visual representation)…”
Section: Overviewmentioning
confidence: 99%
“…Studies were most often published in conference proceedings in fields related to interdisciplinary research on intelligent virtual agents and human-computer interactions, with fewer published in health-related fields. No significant effect [48] a , [51] No significant effect [48] a , [51,62] No significant effect [48] a Mixed negative [48] a , [62] 3 (7) Animated avatar (vs no visual representation)…”
Section: Overviewmentioning
confidence: 99%
“…In [15], for instance, species and realism are identified as the key variables of agent appearance. The research indicates different species (human, animal, robots, objects, and mystical creatures) and realism levels (stylization, resolution, and detailedness) which, in later work by the same authors, was demonstrated to have an impact on older people's willingness to interact with an agent [16,17].…”
Section: Experimental Designmentioning
confidence: 89%
“…Three articles researched the design feature agency (Gambino et al, 2019;Sin & Munteanu, 2019;Straßmann et al, 2020). The articles show ambiguous results.…”
Section: Looks (Species)mentioning
confidence: 99%
“…Three articles researched the design feature rendering style Mostajeran et al, 2019;Straßmann et al, 2020). The articles show no effect of the ECA's rendering style (realistic or cartoony) on user's intention to use (Straßmann et al, 2020), (intention towards) behaviour change , usability and user experience (Straßmann et al, 2020), the user's perception of the ECA's characteristics , perceived realism, likeability, trustworthiness, competence, attractiveness and sociability (Straßmann et al, 2020) and the user's relation with the ECA (Straßmann et al, 2020). However, a study by Mostajeran et al shows an effect of the ECA's rendering style.…”
Section: Looks (Realism)mentioning
confidence: 99%
See 1 more Smart Citation